A expansão urbana de Belo Horizonte e da Região Metropolitana de Belo Horizonte: o caso específico do município de Ribeirão das Neves - Joseane de Souza (2008)
This work analyses the urban expansion of BH and of the RMBH with emphasis on that expansion towards Ribeirão das Neves, in the North-Centre Vector. The urban expansion of BH and RMBH is more and more related to internal migration, mainly, those of intrametropolitan character and also to the improvement of the road system, for allowing the intensification of the pendular movement.The expansion of BH, sint its inauguration, has been taking place, with priority, towards the West and North regions of the urban community, determining the RMBH expansion in the same directions.For the North-Centre Vector, the city of Ribeirão das Neves has been establishing as the residential place for the pour people, and also as dormitory city. It is one of the poorest cities of all the RMBH, wich has been changing into the main front of metropolitan expansion.